Faktor-Faktor Yang Mempengaruhi Kualitas Informasi Laporan Keuangan Pemerintah Daerah (Studi Empiris Pada OPD Kabupaten Gunungkidul) - Adhivinna, Vidya Vitta; Hikmahwati, Ariyanti Nurul (AKMENIKA, 2020)
This study aims to examine the effect of competency of human resources, utilization of information technology, government internal control system, and regional financial accounting system on the information quality of local government financial statement.Data was collected by distributing questionnaires to 28 regional government organization of Gunungkidul Regency. Sampling using a Purposive Sampling technique with criteria is employees who work in the accounting or financial administration with respondents are 72 people. Data were analyzed using SPSS program version 16 and hypothesis testing using multiple linear regression analysis.The results showed that partially, human resource competency, utilization of information technology and government internal control system did not affect the information quality of local government financial statement, while the regional financial accounting system affected the information quality of local government financial statement. Simultaneously, HR competency, utilization of IT, government internal control system, and regional financial accounting system affect the information quality of local government financial statement.Keywords: information quality of local government financial statement, human resource competency, utilization of IT, government internal control system, and regional financial accounting system.